Nutritional status and dietary patterns of children with attention deficit hyperactivity disorder in Bangladesh - Huq, Abul Kashem Obidul; Mony, Sakera Khatun; Chowdhury, Totini Datta; Uddin, Ielias; Rahim, Abu Naim Mohammad Bazlur; Jahan, Tasrin; Moon, Khaleda Hossain; Hasin, Chowdhury Tasneem; Haque, Kazi Mohammad Formuzul (Intelektual Pustaka Media Utama, 2023)
A descriptive cross-sectional study was conducted purposively among 45 children who took regular health and nutritional care facilities in the Savoy Autism Rehabilitation Center at Narayanganj, Bangladesh with the aimed to observe the nutritional status and dietary patterns of the selected attention deficit hyperactivity disorder (ADHD) child. About 24% of the respondents were well nourished, while 18% of respondents were overweight and 58% of the children were underweight. Dietary patterns were monotonous, cereals (rice/bread) consumption were higher, whereas daily fish and meat consumption were very poor such as 4.4% (small fish), 13.3% (large fish), and 2.2% (meat) respectively daily. Fruits and vegetables consumption were also found as poor among the children. It can be concluded that more emphasis should be given to the incorporation of meat, fish, fruits and vegetables daily into the diet of children with providing nutritional care guidelines to the caregivers of these children so that their diet gets more diversified to ensure macro and micronutrient adequacy. Diet rich with adequate nutrients and proper behavioral and psychiatric therapy should be provided in order to control hyperactive-related disorders.